2022
DOI: 10.21203/rs.3.rs-2156463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Prototype For Quantum Database In Hybrid Quantum: A Complete Ecosystem

Abstract: This study proposes a prototypeAnd a possibility to converge both this quantum database and classical database. This study mostly identifies the gap between this classical database and quantum database and it proposes a hypothesis and prototype which can be implemented in future products. It is a way that can be used in future industrial product development on hybrid quantum computers. The existing concept used to consider oracle as a black box this study opens up the possibility for the quantum industry to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Quantum computing holds an immense amount of capabilities to solve any classical problems that are unresolved. Apart from the problems in the classical computer, it is shown that quantum query complexity-related problems are still unresolved [ [17,31,53,79]]. Quantum computing mostly developed theoretically with few well-known components QKD(quantum key Distribution)[ [7,17,31,79]],…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantum computing holds an immense amount of capabilities to solve any classical problems that are unresolved. Apart from the problems in the classical computer, it is shown that quantum query complexity-related problems are still unresolved [ [17,31,53,79]]. Quantum computing mostly developed theoretically with few well-known components QKD(quantum key Distribution)[ [7,17,31,79]],…”
Section: Introductionmentioning
confidence: 99%
“…Entagle [[7, 17, 31, 79]], Teleporation[ [7,17,31,79]], quantum dot, spin qubit, NV center qubit. Within the Quantum Search Algorithm, the quantum oracle is considered a black box that has only one operation to perform i.e....improving the performance of searching operations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations